2017
DOI: 10.1038/s41598-017-03831-5
|View full text |Cite
|
Sign up to set email alerts
|

Iodine-125 Brachytherapy Prophylaxis after Radiofrequency Ablation Cannot Benefit Patients in High Risk of Locoregional Hepatocellular Carcinoma Recurrence

Abstract: This study evaluated if iodine-125 brachytherapy prophylaxis after radiofrequency ablation (RFA) prolongs time to recurrence (TTR) and overall survival (OS) of patients in high risk of locoregional hepatocellular carcinoma (HCC) recurrence. 116 patients with total tumor necrosis after RFA were divided into iodine-125 brachytherapy prophylaxis treatment group and control group. The primary endpoint was TTR, and secondary endpoints were OS and treatment-related adverse events. There were no significant differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
1
7
0
Order By: Relevance
“…The technical success rate, i.e., completion according to plan, in our study was 100%, which is in line with reports from the literature [5,18]. The primary technical efficacy was 97.5%, also comparable with reported primary technical efficacy rates after conventional RF ablation in the hepatic dome ranging from 86.7% [5] to 93.2-96% [19,20]. The conventionally treated tumors were smaller (median diameter 1.7 cm and maximal diameter 4 cm) compared with our study with a median tumor size of 2.2 cm and a maximal diameter of 10 cm.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The technical success rate, i.e., completion according to plan, in our study was 100%, which is in line with reports from the literature [5,18]. The primary technical efficacy was 97.5%, also comparable with reported primary technical efficacy rates after conventional RF ablation in the hepatic dome ranging from 86.7% [5] to 93.2-96% [19,20]. The conventionally treated tumors were smaller (median diameter 1.7 cm and maximal diameter 4 cm) compared with our study with a median tumor size of 2.2 cm and a maximal diameter of 10 cm.…”
Section: Discussionsupporting
confidence: 91%
“…According to the in-surgical studies that primarily used Clavien-Dindo classification [30], the major complicate rate in the present study was 4.9% (10/204). Major complication rates after laparoscopic RFA were 10% and 12.4%, respectively [20,31]. Several surgical studies report significantly higher major complicate rates of 10-27% after LLR, and 18-37% after open resection, respectively [10,[32][33][34][35].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that 125 I brachytherapy can achieve high locoregional tumors control ( 35 ). The study by Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…The application of TACE is also limited due to the extrahepatic collateral arteries and the non-dense deposition of iodide oil (6,11). It has been reported that 125 I brachytherapy can achieve high locoregional tumors control (35). The study by Chen et al (27) showed that compared with RFA alone, RFA combined with 125 I seeds implantation could significantly improve OS and cumulative recurrence in patients with small HCCs.…”
Section: Discussionmentioning
confidence: 99%